Current Trends and Emerging Strategies in Friction Stir Spot Welding for Lightweight Structures: Innovations in Tool Design, Robotics, and Composite Reinforcement—A Review - Suresh Subramanian; Elango Natarajan; Ali Khalfallah; Gopal Pudhupalayam Muthukutti; Reza Beygi; Borhen Louhichi; Ramesh Sengottuvel; Chun Kit Ang (Crystals)
Friction stir spot welding (FSSW) is a solid-state joining technique increasingly favored in industries requiring high-quality, defect-free welds in lightweight and durable structures, such as the automotive, aerospace, and marine industries. This review examines the current advancements in FSSW, focusing on the relationships between microstructure, properties, and performance under load. FSSW offers numerous benefits over traditional welding, particularly for joining both similar and dissimilar materials. Key process parameters, including tool design, rotational speed, axial force, and dwell time, are discussed for their impact on weld quality. Innovations in robotics are enhancing FSSW’s accuracy and efficiency, while numerical simulations aid in optimizing process parameters and predicting material behavior. The addition of nano/microparticles, such as carbon nanotubes and graphene, has further improved weld strength and thermal stability. This review identifies areas for future research, including refining robotic programming, using artificial intelligence for autonomous welding, and exploring nano/microparticle reinforcement in FSSW composites. FSSW continues to advance solid-state joining technologies, providing critical insights for optimizing weld quality in sheet material applications.